Shifting sands - Enoch, Wesley; Sen, Ivan; Olive, Mark; Glynn, Erica; Torres, Mitch; Maclean, Danielle; Australian Film Commission. Indigenous Branch (New South Wales: Film Australia, 1995)
A series of short films featuring Aboriginal actors and Aboriginal themes
Grace / Wesley Enoch (15.00) -Tears / Ivan Sen (16 min.) - Passing through / Mark Olive (13 min.) - My bed your bed / Erica Glynn [16 min.] - Promise / Mitch Torres [10 min] -My colour, your kind / Danielle Maclean [11 min. ]
Keywords: Aboriginal Australians -- Social life and customs -- Drama; Aboriginal Australians -- Drama; Short films -- Australia